Experiencing America's story through fiction : historical novels for grades 7-12 - Crew, Hilary S., 1942- (Chicago : ALA Editions, An imprint of the American Library Association, 2014)
An annotated bibliography covering historical novels about the United States from the colonial period to the era of the Iraq War. Ideal for school librarians, history teachers, and public librarians working with youth. The titles were published between 2000 and 2013, and are appropriate for seventh to twelfth graders.
Colonization and settlement (1585-1759) -- Revolution and the New Nation (1760-1820s) -- Expansion and reform (1801-1870) -- The Civil War and Reconstruction (1850-1877) -- Development of the Industrial United States (1870-1899) -- Emergence of Modern America and World War I (1900-1928) -- The Great Depression and World War II (1929-1945) -- Postwar United States (1945-1979) -- Contemporary America (1980-)
Includes bibliographical references (pages 183-185) and index.
Keywords: Historical fiction, American -- Bibliography; Young adult fiction, American -- Bibliography; Children's stories, American -- Bibliography; Historical fiction, American -- Stories, plots, etc; Young adult fiction, American -- Stories, plots, etc; Children's stories, American -- Stories, plots, etc; United States -- History -- Fiction -- Bibliography; United States -- In literature -- Bibliography; Teenagers -- Books and reading -- United States